Efektivitas Pembiayaan Usaha Mikro Kecil Menengah (UMKM) Bank Pembiayaan Rakyat Syari’ah (BPRS) Gayo terhadap Pemberdayaan Ekonomi Masyarakat Aceh Tengah - Isara Abda Noka (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2019)
The Syari'ah People's Financing Bank (BPRS) has a considerable contribution in supporting the development of Micro, Small and Medium Enterprises (MSMEs). BPRS Gayo has contributed to the economic development of the people of Central Aceh, especially in Micro, Small and Medium Enterprises. But the reality in the field is that there are still many people who run businesses and businesses, especially the users and recipients of financing from BPRS Gayo that have not experienced significant business development. Based on that phenomenon, this research is intended to see the effectiveness of financing of BPRS Gayo Micro Small and Medium Enterprises towards the economic empowerment of the people of Central Aceh. The results of the study show that the financing applied in BPRS Gayo is only through aqad murabahah. Murabahah financing is classified as a safe type of financing and the risk of loss is very low. The funding channeled by BPRS Gayo for the empowerment of the community's economy is effective, seen from the increase in income, business stability and welfare felt by customers.